2008
DOI: 10.1179/000870408x311422
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Relevance and Cognition in Attention-guiding Geovisualisation

Abstract: It is a delicate task to design suitable geovisualisations that allow users an efficient visual processing of the depicted geographic information. Today, such a design task is subject to three major challenges: the ever growing amount of geospatial data at various levels of detail, the diversified applications of that data, and the continuously expanding range of display sizes. In this work, the aim was to enhance the visualisation of relevant geographic information by focusing on utility and usability issues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 34 publications
(30 reference statements)
0
26
0
Order By: Relevance
“…One key objective in designing the 3D map is to ensure effective and efficient transmission of cartographic information to users. Swienty et al [35] proposed a general framework for geovisualization called "attention-guiding geovisualization". Its basic principles are to: (1) design task-relevant objects that are perceptually salient; (2) make less relevant objects less attractive; and (3) omit irrelevant objects [35].…”
Section: Designing the 3d Mapmentioning
confidence: 99%
See 4 more Smart Citations
“…One key objective in designing the 3D map is to ensure effective and efficient transmission of cartographic information to users. Swienty et al [35] proposed a general framework for geovisualization called "attention-guiding geovisualization". Its basic principles are to: (1) design task-relevant objects that are perceptually salient; (2) make less relevant objects less attractive; and (3) omit irrelevant objects [35].…”
Section: Designing the 3d Mapmentioning
confidence: 99%
“…Swienty et al [35] proposed a general framework for geovisualization called "attention-guiding geovisualization". Its basic principles are to: (1) design task-relevant objects that are perceptually salient; (2) make less relevant objects less attractive; and (3) omit irrelevant objects [35]. Based on a controlled eye-tracking experiment, Fabrikant et al [36] further demonstrated that perceptually salient designs can contribute to efficient spatial inference making for novice users when interpreting weather maps.…”
Section: Designing the 3d Mapmentioning
confidence: 99%
See 3 more Smart Citations